2010
DOI: 10.1007/jhep09(2010)042
|View full text |Cite
|
Sign up to set email alerts
|

Extra dimensions in γγ → γγ process at the CERN-LHC

Abstract: Potential of the LHC to explore the phenomenology of the Kaluza-Klein (KK) tower of gravitons in the scenarios of the Arkani-Hamed, Dimopoulos and Dvali(ADD) model and Randall-Sundrum (RS) model is discussed via the process γγ → γγ including the Standard Model one loop diagram. The improved constraints on model parameters have been obtained compared to the LEP and Tevatron sensitivity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 37 publications
(22 reference statements)
0
26
0
Order By: Relevance
“…The exclusive production of pairs of muons and pairs of W bosons have been generated using the Herwig++ generator [8]. The exclusive production of pairs of photons has been generated using the FPMC generator [9] at large W γ γ where the γ γ → γ γ cross section is dominated by one-loop diagrams involving W bosons [10]. Finally, the exclusive production of the Higgs boson is computed according to higgs effective field theory (HEFT) [11].…”
Section: Introductionmentioning
confidence: 99%
“…The exclusive production of pairs of muons and pairs of W bosons have been generated using the Herwig++ generator [8]. The exclusive production of pairs of photons has been generated using the FPMC generator [9] at large W γ γ where the γ γ → γ γ cross section is dominated by one-loop diagrams involving W bosons [10]. Finally, the exclusive production of the Higgs boson is computed according to higgs effective field theory (HEFT) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using proton-tagging at the LHC for New Physics searches can be found in refs. [3,4,[9][10][11][12][13][14][15][16][17][18][19]. We refer to [20] for a study of light-by-light scattering at the LHC without proton tagging.…”
Section: Jhep02(2015)165 1 Introductionmentioning
confidence: 99%
“…Experimental results on exclusive twophoton production of W + W − and + − pairs in γ γ interactions reported by the CMS and ATLAS Collaborations [9][10][11][12] have demonstrated that it is possible to measure such events with the experimental apparatus already available at the LHC, allowing for novel studies of QCD at very high energies and searches for Beyond Standard Model Physics (see, e.g., Ref. [49][50][51][52][53][54][55][56][57][58][59]). This motivates us to revisit the analysis of double vector meson production in ultra peripheral heavy ion collisions performed some time ago in Refs.…”
mentioning
confidence: 99%